Optimum active power tracking based control of brushless doubly-fed reluctance generator tied to renewable microgrid - Parida, Adikanda; Paul, Manish (Institute of Advanced Engineering and Science, 2024)
Among all the existing wind energy generators (WEG), a brushless doubly-fed reluctance generator (BDFRG) is the better option in terms of maintenance cost and constructional simplicity. For more adaptability, the efficiency of the BDFRG can be improved through proper control mechanisms. Therefore, this paper presents an optimum active power tracking-based control technique for BDFRG for minimum losses. Copper loss of the machine is considered to be the objective function for the proposed optimization technique. However, one issue found to be the major in all the existing controllers is the accuracy of sensor less control of the BDFRG. Therefore, this paper proposes an accurate model reference adaptive system (MRAS) based sensor less mechanism for computation of BDFRG secondary winding flux position. The no sensitivity of the proposed technique to the machine parameter variation and hence the accuracy, catch-on-fly, and non-inclusion of integrator and differentiators and hence less burden on the processor makes the proposed scheme robust. The control scheme is practically implemented with a 2.5 kW BDFRG using MATLAB/Simulink platform.